How practical are transmucosal fentanyl products for breakthrough cancer pain? novel use of placebo formulations to survey user opinion. Issue 3 (2nd September 2011) - England, Ruth; Maddocks, Matthew; Manderson, Cathann; Zadora-Chrzastowska, Sonja; Wilcock, Andrew
Abstract : Background: Three transmucosal fentanyl products have recently been licensed for cancer-related breakthrough pain: a sublingual tablet, a buccal/sublingual tablet and a nasal spray. Limited comparative data hinder identifying the most appropriate to use and adopt onto a service formulary. However, the availability of placebo formulations provides a unique opportunity to compare the practical aspects of their use. Methods: 30 patients with cancer accessed and administered a placebo of each product and were asked to rate them using 1–7 Likert agree–disagree scales and free-text responses, with regard to ease of access and administration, palatability and overall impression. Participants rated their usual rescue analgesic similarly, based on recall. They also indicated whether they would be prepared to use the fentanyl product, and their most preferred. Results: For accessibility, the usual rescue analgesic was rated best (median score 3), significantly better than the buccal/sublingual tablet (p=0.01) and nasal spray (p<0.01), but not the sublingual tablet. Conversely, the nasal spray was rated significantly worse (median score 7) than the others (p<0.01). For ease of administration, the usual rescue analgesic and sublingual tablet were rated equally best (median score 1), with only the latter being significantly different to the buccal/sublingual tablet (p=0.04) and nasal spray (p=0.05). For palatability, the sublingual tablet was rated the best (median score 2), but was significantly different only to the buccal/sublingual tablet (p<0.01). For overall impression, the sublingual tablet was rated significantly better (median score 3) than the others, with more patients prepared to use it and selecting it as their most preferred (27 and 18, respectively). Conclusion: This survey provides valuable insight into the practical aspects of these three transmucosal fentanyl products for practitioners considering their use.